1)rút gọn : $\frac{sin 90cos36-cos90sin36}{cos\frac{3\pi}{5}.cos\frac{\pi}{5}-sin\frac{\pi}{5}.sin\frac{\pi}{5}}$
2) khai triển tan(a+b+c) theo tan a, tan b,tan c
giải
1.
$\frac{sin 90cos36-cos90sin36}{cos\frac{3\pi}{5}.cos\frac{\pi}{5}-sin\frac{\pi}{5}.sin\frac{\pi}{5}} = \frac{sin(90-36)}{cos(\frac{3\pi}{5}+\frac{\pi}{5})} = \frac{sin54}{cos144} = -\frac{cos36}{cos36} = -1$
2.
$tan ( a + b + c ) = tan [(a+b) + c )] = \frac{tan(a+b)+ tanc}{1-tan(a+b)tanc} = \frac{\frac{tana +tanb}{1 - tanatanb}+ tanc}{1 - \frac{tana + tanb}{1 - tanatanb}tanc}$
đến đây bạn có thể quy đồng mẫu số rồi làm tiếp cũng được